104k views
0 votes
Solve 10 + 6(–9 – 4x) = 10(x – 12) + 8.

A. x = 2
B. x = –6
C. x = –18
D. x = 17

2 Answers

4 votes

Answer:

Solve for x by simplifying, both sides of the equation then isolating the variable So the Answer is x = 2 Hope this helps :)

Explanation:


User Dragan Marjanovic
by
6.3k points
7 votes

Answer:

x=2 Choice A

Explanation:

10 + 6(–9 – 4x) = 10(x – 12) + 8.

distribute

10 + 6*(-9 + 6* (-4x) = 10 *x - 10*12 +8

multiply

10 -54 -24x = 10x-120+8

combine like terms

-44 -24x = 10x -112

add 24x to each side

-44 -24x+24x = 10x+24x -112

-44 = 34x-112

add 112 to each side

68 = 34x

divide by 34 on each side

68/34 = 34x/34

2 =x


User Yannan Wang
by
5.9k points